The major supervisory initiatives post-FDICIA: Are they based on the goals of PCA? Should they be? - Robert A. Eisenbeis; Larry D. Wall (Federal Reserve Bank of Atlanta, 2002)
The prompt corrective action provisions in FDICIA 1991 provide the supervisors with an unambiguous goal: "to resolve the problems of insured depository institutions at the least possible long-term cost to the deposit insurance fund." Yet performance of the regulators in achieving this goal has been lacking in that substantial losses continue to be imposed on the insurance funds when banks fail. Is PCA misguided, or are there incentive defects in the law and how the requirements are being administered? This paper analyzes these issues in the context of recent proposals to reform the deposit insurance system.
Keywords: 330; Federal Deposit Insurance Corporation Improvement Act of 1991; Financial institutions; Deposit insurance; Bank supervision